Persepsi Masyarakat Kelurahan Baru Kota Makassar Terhadap “Gerakan Makassar Gemar Membaca” - Syahrir, Mohammad (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Gerakan Makassar Gemar Membaca (GMGM) or Makassar Love Reading Program is one of the Makassar city government’s programs in which it has been alreading running since several years ago. The program was proposed in order to enhance or create reading habit culture for the citizens. This study is a case study to figure out the perception of the citizens about the GMGM. The study took a reading area as a research location in Kelurahan Baru , Makassar city. The study found that the GMGM has been highly appreciated by the citizens, especially in Kelurahan Baru citizens. Nonetheless, its remains certain barriers, for instances; the lack of awreness of the citizens about reading, and the program was not widely informed by the government for all of citizens. Besides, the study also figured out some of real implementations of the program like creating reading volunteers, librarianship workshop, reading competition, and providing internet access for the reading areas.